A Perspective from the Field: The Disconnect between Abstinence-Based Programs and the Use of Motivational Interviewing in Treating Substance Use Disorders. Issue 1 (2nd January 2018) - Gallagher, John Robert; Bremer, Traci
ABSTRACT: Motivational Interviewing was first introduced nearly three-and-a-half decades ago and has been used to treat a range of problems, including substance use disorders (SUDs). Treating SUDs is complex, and there is no universal philosophy of treatment. Rather, throughout the disciplines history, two distinctly different philosophies of treatment have emerged: total abstinence and harm reduction. In this article, the authors discuss how motivational interviewing is best aligned with harm-reduction approaches, and how motivational interviewing cannot be used in its fidelity in abstinence-based programs, despite many abstinence-based programs claiming to do so. The authors highlight examples on the disconnect between abstinence-based programs and the four main principles of motivational interviewing: (1) deemphasizing labels used in treatment, (2) increasing individual responsibility, (3) increasing internal attribution (being responsible for one's own situation and future changes instead of placing responsibility on external factors), and (4) increasing one's awareness of cognitive dissonance (finding consistency between desires and actions). Motivational interviewing, when used in its fidelity, has consistently demonstrated effectiveness in reducing problematic drug use, improving engagement and retention in treatment, and increasing overall quality of life. As a result, the authors encourage agencies and counselors who treat SUDs to utilize a harm reduction philosophy in combination with motivational interviewing techniques to best serve our clients.